The effects of Cr/Mo micro-alloying on the corrosion behavior of carbon steel in CO2-saturated (sweet) brine under hydrodynamic control - Sk,MH; Abdullah,AM; Qi,J; Ko,M; Ingham,B; Laycock,N; Ryan,MP; Williams,DE (JOURNAL OF THE ELECTROCHEMICAL SOCIETY, 2018)
The effects of micro-alloying of plain carbon steel with Cr and Mo on the corrosion behavior in CO2-saturated (sweet) brine (0.5 MNaCl, pH 6.6) environment, under hydrodynamic conditions, at 80C were investigated. Crystalline siderite/chukanovite scalesformed on all the alloys. Analysis of potentiostatic current transient data suggest that there exists a synergistic interaction betweenCr and Mo, which induces more rapid crystallization of the scale compared to Mo-free steels. Increasing the Mo content alsosuppressed the transport-dependent dissolution current passing through the initially-present amorphous surface film. TEM imagesof the FIB-sectioned corrosion scales confirm that the corrosion scale formed on 1Cr0.7Mo is comparatively thinner and yet offersgreater protectiveness when compared to the plain carbon steel.